Electrically surface-driven switchable wettability of liquid crystal/polymer composite film - Chiu, Ya-Ping; Shen, Cheng-Yu; Wang, Wen-Ching; Chu, Ting-Yu; Lin, Yi-Hsin (My University, 2010)
This study demonstrates the electrical control of the surface wettability of liquid crystal and polymer composite film. The application of external voltages significantly affects the surface wettability of the film. This study uses atomic force microscopy to quantitatively characterize the fundamental mechanism responsible for the structurally driven changes in surface properties at various applied voltages. The surface wettability transitions of the film are electrically driven, as shown by reorganized liquid crystal molecules. Measurements of the voltage-dependent surface wettability of the composite film suggest approaches to supporting control applications of future electro-optical nanotechnology devices.
Keywords: atomic force microscopy; composite materials; liquid crystals; polymer films; surface structure; wetting